Design High Throughput Data Center Topology Network Berbasis Random Graph - Aziza Hayupratiwi; Sidik Prabowo; Muhammad Arief Nugroho (eProceedings of Engineering, 2019)
AbstrakSalah satu peningkatan kinerja dalam Data Center (DC) adalah dengan membuat desain topologipada Data Center Networks (DCNs). Pengaruh desain network dalam data center akan berpengaruhterhadap penging- katan nilai throughput dalam jaringan. Dalam topologi Data Center Networks,desain terbagi menjadi dua yaitu homogeneous dan heterogeneous. Homogeneous topology designdiatur dengan sejumlah port dan swi- tch yang sama dan dapat mencapai high throughputdengan low cost. Namun, pada jaringan heterogeneous belum dapat mencapai high throughput.Dalam tugas akhir ini dilakukan implementasi desain topologi pada data center berbasisrandom graph. Hasil yang diperoleh pada penelitian ini membuktikan bahwa ja- ringanheterogeneous dengan 40 dan 32 degree dapat mencapai high throughput jika dibandingkandengan jaringan heterogeneous 24 dan 8 degree serta jaringan homogeneous 16 degree. Kata Kunci: Throughput, Data Center Networks, Homogeneous, Heterogeneous, Topology Design. AbstractOne of the Performance Improvements in Data Centers (DC) is to create topology designs in Data CenterNetworks (DCNs). The influence of network design in the data center will affect the increase in value of throughput in the network. In the Data Center Network topology, the design isdivided into two hetero- geneous and heterogeneous forms. Homogeneous topology design withthe same portfolios added and can achieve high throughput with low costs. However, theheterogeneous network has not been able to achieve high throughput. In this final project, theimplementation of topological data design in the basis of random graphs. The results obtained inthis study prove that a heterogeneous network with 40 and 32 can achieve high throughput ifcompared to a heterogeneous network of 24 and 8 degrees and a homogeneous network of 16degrees Keywords: Throughput, Data Center Networks, Homogeneous, Heterogeneous, TopologyDesign